Planetary citizenship : your values, beliefs, and actions can shape a sustainable world - Henderson, Hazel, c1933.; Ikeda, Daisaku (Santa Monica, CA : Middleway Press, 2004)
Global activists Hazel Henderson and Daisaku Ikeda explain how ordinary citizens can take responsibility for creating a more sustainable environment, discussing the spiritual values needed, and describing how people have made positive changes in families, communities, and countries.
Translation of: Chikyu taidan kagayaku josei no seiki he.
Includes bibliographical references (p. [177]-178) and index.
Adult.
Adult
Keywords: Environmental protection; Environmentalism; Sustainable development -- Citizen participation; Sustainable development -- Citizen participation